2016
DOI: 10.1007/s10863-016-9649-9
|View full text |Cite
|
Sign up to set email alerts
|

P2X7R large pore is partially blocked by pore forming proteins antagonists in astrocytes

Abstract: The ATP-gated P2X7R (P2X7R) is a channel, which is involved in events, such as inflammation, cell death, and pain. The most intriguing event concerning P2X7R functions is the phenomenon of pore dilation. Once P2X7R is activated, the permeability of the plasma membrane becomes higher, leading to the permeation of 1000 Da-weight solutes. The mechanisms involved in this process remain unclear. Nevertheless, this event is not exclusively through P2X7R, as other proteins may form large pores in the plasma membrane.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…The IC 50 of 2354glu for [Ca 2+ ] i was 148 μM. ATP is known to elicit membrane pore dilatation by activating P2X7 receptors followed by cytolysis to trigger IL‐1β maturation (Faria, Reis, Ferreira, Cezar‐de‐Mello, & Moraes, ; Takenouchi et al, ; Wewers, ). Thus, we examined whether 2354glu prevented P2X7 receptor‐mediated pore formation in THP‐1 macrophages using PI uptake.…”
Section: Resultsmentioning
confidence: 99%
“…The IC 50 of 2354glu for [Ca 2+ ] i was 148 μM. ATP is known to elicit membrane pore dilatation by activating P2X7 receptors followed by cytolysis to trigger IL‐1β maturation (Faria, Reis, Ferreira, Cezar‐de‐Mello, & Moraes, ; Takenouchi et al, ; Wewers, ). Thus, we examined whether 2354glu prevented P2X7 receptor‐mediated pore formation in THP‐1 macrophages using PI uptake.…”
Section: Resultsmentioning
confidence: 99%
“…Avian Müller cells in culture express P2X7 receptors [ 28 ] and ATP is known to permeabilize mice cortical astrocytes [ 22 ] through a phenomenon described as pore dilation. Propidium iodide (PI, MW 668), is a molecule commonly used to measure cell permeabilization Therefore, we asked if addition of ATP or GSH to avian Müller cells in culture could induce PI uptake in a P2X7 receptor dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…For positive control of TUNEL, cells were treated with the inhibitor of the endoplasmic reticulum calcium ATPase thapsigargin. Previously, we described that thapsigargin induces apoptosis of photoreceptors in rat retinal tissue [ 22 ]. Here, we show that treatment with 30nM thapsigargin, for 24 hours, dramatically increases TUNEL positive cells ( Fig 8C ) in chicken retinal cell culture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When open, they allow for the passage of molecules of up to 1,000 Da without necessarily leading to cell death. Among pore-forming proteins, pannexin-1 [ 54 ], connexin hemichannels [ 55 ], TRPV1-4 subtypes and TRPA1 [ 56 ], calcium homeostasis modulator 1 (CALHM1) [ 57 ], Maxi anion [ 58 ], plasma membrane VDAC [ 59 ] and ATP-gated subtypes P2×2 [ 60 62 ], P2×4 [ 63 65 ] and, especially, P2×7 receptors [ 66 68 ] are noteworthy (Figure 2 ). One possibility would be to study the involvement of the P2×7 associated-pore as an MB uptake route in the cytoplasm of neoplastic cells, and, in this regard, we have recently demonstrated that P2×7 can function as a drug delivery system in the J774 tumor cell line [ 69 ].…”
Section: Introductionmentioning
confidence: 99%